Short term heat acclimation reduces heat strain during a first, but not second, consecutive exercise-heat exposure - Pryor, R. R.; Pryor, J. L.; Vandermark, L. W.; Adams, E. L.; Brodeur, R. M.; Armstrong, L. E.; Lee, E. C.; Maresh, C. M.; Casa, D. J. (Journal of Science and Medicine in Sport, 2021)
Objectives: Determine whether five days of heat acclimation reduces cardiovascular and thermoregulatory strain during consecutive exercise-heat exposures on the sixth day in the heat. Design: Pair-matched randomized control trial. Methods: Twenty-four males completed two, 120 min exercise sessions (Session 1, Session 2) in a single day before (Day 1) and after (Day 6) four additional days of exercise in either hot (HOT: 40 °C, 40% relative humidity, n = 16) or temperate (CON: 23 °C, 25% relative humidity, n = 8) environments. A mixed-methods heat acclimation approach was implemented. Day 2 consisted of 120 min of moderate-high intensity treadmill exercise. Days 3-5 consisted of 90 min of moderate-high intensity exercise, with HOT completing this in a hyperthermia clamped manner at rectal temperature =38.5 °C, and CON < 38.5 °C. Results: Session 1 end of exercise rectal temperature and heart rate were lower on Day 6 compared to Day 1 for HOT (p = 0.012, p = 0.003) but not CON (p = 0.152, p = 0.437). Session 2 end of exercise rectal temperature was not different between days for HOT (p = 0.104) or CON (p = 0.275). Session 2 end of exercise heart rate was lower on Day 6 compared to Day 1 for HOT (p = 0.004) and CON (p = 0.039). Session 1 sweat sensitivity was greater on Day 6 compared to Day 1 for HOT (p = 0.039) but not CON (p = 0.257). Sweat rate was unchanged for HOT and CON between days during Session 1 (p = 0.184, p = 0.962) and Session 2 (p = 0.051, p = 0.793), respectively. Conclusions: Five days of heat acclimation reduced cardiovascular strain but not thermoregulatory strain during the second, consecutive exercise-heat exposure.